Awareness of cervical cancer risk factors and symptoms and lay beliefs amongst women recently diagnosed with cervical cancer in South Africa and Zimbabwe - Govender, Sudarshan (Department of Public Health and Family Medicine, 2025)
Background: Despite South Africa (SA) and Zimbabwe having nationwide cervical cancer screening and human papillomavirus (HPV) vaccination programs, the incidence and mortality rates of cervical cancer remain high in these countries. We explored awareness of cervical cancer symptoms and risk factors as well as lay beliefs amongst women recently diagnosed with cervical cancer from SA and Zimbabwe. Methods: This is a secondary analysis of data from a descriptive cross-sectional study of women recently diagnosed with cervical cancer in SA and Zimbabwe. Between September 2022 and November 2023 women from selected health care facilities who were either recently diagnosed with cervical cancer or were within four weeks of being told their treatment plan were invited to participate in the study. Data were collected by interviewers using a locally validated questionnaire. Unprompted, open-ended questions were used to assess participant awareness of cervical cancer symptoms and risk factors. In analysis, we described awareness of cervical cancer symptoms and risk factors (zero versus ≥1 known) and reported lay beliefs. Logistic regression was used to examine associations between sociodemographic variables and awareness stratified by country. Results: Among 506 women enrolled (56.1% from SA; 43.9% from Zimbabwe), 54.3% (274) were able to recall ≥1 correct symptom of cervical cancer. This proportion was higher among women from Zimbabwe (73.4%) than SA (26.6%). Only 18.8% (95) of women were able to recall ≥1 correct risk factor for cervical cancer (73.7% from Zimbabwe versus 26.3% from SA). Overall, important risk factors including HPV infection, HIV and not going for screening were known by very few women (0.8%, 3.4% and 1.4% respectively). There were no statistically significant sociodemographic predictors of symptom awareness in Zimbabwe. In SA, women who completed secondary education, lived in a peri-urban setting or who knew a family member or friend with cancer were significantly more likely to know ≥1 cervical cancer symptom compared to those with less than secondary school (aOR 2.84 95% CI 1.33-6.12), those who lived in a rural setting (aOR 4.99 95% CI 1.36-18.81) or those who did not know anyone with cancer (aOR 2.61 95% CI 1.38-4.98). For risk factor awareness, among South African women, those who completed secondary school were significantly more likely to know ≥1 cervical cancer risk factor compared to those with less than secondary school (aOR 2.86 95% CI 1.05- 7.69). Among Zimbabwean women, those in the second highest wealth index or who were known to be living with HIV were significantly more likely to know ≥1 cervical cancer risk factor compared to those in the poorest wealth index (aOR 5.69 95% CI 1.21-29.24) or those who were not living with HIV (aOR 2.14 95% CI 1.04-4.50). Overall, 90 (17.9%) women mentioned at least one lay belief about risk factors for cervical cancer. The most commonly reported risk lay belief was inserting herbs, creams, or objects into the vagina (8.7%). Conclusion: The awareness of cervical cancer symptoms and risk factors amongst women with cervical cancer was low, particularly in SA. There is an urgent need for interventions to improve knowledge around cervical cancer, as low levels of awareness can impact timely cancer diagnosis and limit the uptake of cervical cancer prevention programs.